A Comprehensive and Systematic Analysis Revealed the Role of ADAR1 in Pan-Cancer Prognosis and Immune Implications. (21st February 2023) - Zhu, Jianlin; Zheng, Jianjian; Zhang, Jinjun; Wang, Songyu; Wang, Lu; Zhao, Yan
Abstract : Adenosine deaminase RNA specific 1 (ADAR1) has been identified as an enzyme that deaminates adenosine within the dsRNA region to produce inosine, whose amplification reinforced the exhaustion of the immune system. Although there were currently cellular and animal assays supporting the relationship between ADAR1 and specific cancers, there was no correlation analysis that has been performed at the pan-cancer level. Therefore, we first analyzed the expression of ADAR1 in 33 cancers based on the TCGA (The Cancer Genome Atlas) database. ADAR1 was highly expressed in most cancers, and there was a closely association between ADAR1 expression and prognosis of patients. Furthermore, pathway enrichment analysis revealed that ADAR1 was involved in multiple antigens presenting and processing inflammatory and interferon pathways. Moreover, ADAR1 expression was positively correlated with CD8 + T cell infiltration levels in renal papillary cell carcinoma, prostate cancer, and endometrial cancer and negatively correlated with Treg cell infiltration. In addition, we further found that ADAR1 expression was closely associated with various immune checkpoints and chemokines. Meanwhile, we observed that ADAR1 may be involved in the regulation of pan-cancer stemness. In conclusion, we provided a comprehensive understanding of the oncogenic role of ADAR1 in pan-cancer, and ADAR1 might serve as a new potential target for antitumor therapy.